Desigualdade de gênero em rendimentos no mercado de trabalho mineiro: o papel das firmas e das ocupações - Nara Lívia de França Morais (2023)
Despite the transformations the labor market has experienced, women still earn less than men. To that extent, this dissertation seeks to discuss the role of firms and occupations in the permanence of gender earnings inequality in Minas Gerais. Using RAIS microdata, we estimate linear hierarchical models for firms and occupations in Minas Gerais during 2015-2019. We find that gender earnings inequality remains even when controlling for characteristics of the workers (sex, age, tenure, contracted hours) and the firm’s and occupations’ composition. Female-dominated occupations are associated with an earnings penalty and lower gender pay inequality. Smaller and female-dominated firms are associated with lower average earnings and less intense gender pay inequality. In short, men and women continue to be unequally paid in the Minas Gerais labor market. And this gap is explained by the gender composition, the proportion of women in leadership positions, and the size of the establishments.